Deployment of Kahoot Media in Indonesian Language Learning Article Material at SMPN 2 Solokan Jeruk: Pemanfaatan Media Kahoot pada Pembelajaran Bahasa Indonesia Materi Artikel di SMPN 2 Solokan Jeruk - Prameswari, Nandini; Yahya, Rachel Khurul Aini; Yusuf, Rian Maulana; Muthmainah, Salsabila; Heryati, Yeti (CV. Media Publikasi Profesional, 2023)
This article aims to analyze the use of the Kahoot application in Indonesian learning in the article material at SMPN 2 Solokan Jeruk. This study uses a descriptive method with a qualitative approach, where data is collected through interviews with relevant teachers. This approach allows researchers to gain in-depth insights into teachers' experiences and views on the application of the Kahoot application in the learning process. The results of the study show that the use of the Kahoot application has a positive impact by creating an interactive and fun learning atmosphere. This application has not only succeeded in increasing students' interest in learning, but also serves as an effective evaluation tool to strengthen students' memory and understanding of the material being taught. Additionally, Kahoot assists teachers in identifying areas that need improvement through direct feedback from students. Thus, this application plays an important role in improving the quality of Indonesian learning at the junior high school level, especially in supporting more modern learning methods that are relevant to students' needs.